An imaging-based RNA interference screen for modulators of the Rab6-mediated Golgi-to-ER pathway in mammalian cells - Heffernan, Linda F.; Suckrau, Pia M.; Banerjee, Teerna; Mysior, Margaritha M.; Simpson, Jeremy C. (Frontiers in Cell and Developmental Biology, 2022)
In mammalian cells, membrane traffic pathways play a critical role in connecting the various compartments of the endomembrane system. Each of these pathways is highly regulated, requiring specific machinery to ensure their fidelity. In the early secretory pathway, transport between the endoplasmic reticulum (ER) and Golgi apparatus is largely regulated via cytoplasmic coat protein complexes that play a role in identifying cargo and forming the transport carriers. The secretory pathway is counterbalanced by the retrograde pathway, which is essential for the recycling of molecules from the Golgi back to the ER. It is believed that there are at least two mechanisms to achieve this - one using the cytoplasmic COPI coat complex, and another, poorly characterised pathway, regulated by the small GTPase Rab6. In this work, we describe a systematic RNA interference screen targeting proteins associated with membrane fusion, in order to identify the machinery responsible for the fusion of Golgi-derived Rab6 carriers at the ER. We not only assess the delivery of Rab6 to the ER, but also one of its cargo molecules, the Shiga-like toxin B-chain. These screens reveal that three proteins, VAMP4, STX5, and SCFD1/SLY1, are all important for the fusion of Rab6 carriers at the ER. Live cell imaging experiments also show that the depletion of SCFD1/SLY1 prevents the membrane fusion event, suggesting that this molecule is an essential regulator of this pathway.